Sharing a Stage in the Arena of Agency: Freedom in Erasmus - Ruler, J. A. van (Erasmus studies, 2024)
Exactly five hundred years ago today, Erasmus engaged with Martin Luther in a debate on free will that continues to inspire, even if it evokes a notion of freedom that is no longer ours in every respect. Emphasising the need for a common-sense reading of Holy Scripture that did not require making conjectures about the existence of hidden forms of divine justice inconsistent with our own, Erasmus confronted Luther with the fact that his “necessitating” notion of grace was not in any way representative of earlier theological positions acknowledging the notion of free will. Refusing to be drawn towards an interpretation of grace that denied human beings the ability to activate the full spectrum of their natural reaction patterns, Erasmus stayed clear of translating earlier theological positions on grace in terms of an overruling of human agency. His theology continued to inspire later generations to work on their moral development rather than to act out of fear for divine retribution. Despite his name as a sceptic and a rhetorician, Erasmus’ decidedly this-worldly interpretation of religious doctrine not only reveals his argumentative agility and deep theoretical insight; it also prompts a universalist approach in theology that consistently favours a predisposition towards the humane.